Aproximation to the trade dress and its impact in the international context: special reference to the international jurisdiction - García Garrido, María Auxiliadora (CUADERNOS DE DERECHO TRANSNACIONAL, 2026)
After studying the concept of trade dress and its jurisprudential origins, this research paper pays particular attention to the regulatory uncertainty surrounding it, analysing the different rules that are applicable by analogy. It compares the treatment of trade dress across different legal systems and focuses on examining the effects of the lack of specific regulation in international proceedings; in particular, on the international jurisdiction from the perspective of European legislation and case law, especially the system that states in the Brussels I bis Regulation and the Lugano Convention.